Tunisia : Selected Issues. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2016)
This paper discusses recent trends, constraints, and opportunities for the future of Tunisia's economy. Tunisia enjoyed solid GDP growth rates in the run-up to the revolution of 2011, driven by the manufacturing and service sectors. A stable macroeconomic environment and a gradual liberalization of trade and investment facilitated growth. Labor has been gradually overshadowed by capital accumulation as the main growth driver, while productivity has been lagging. The existing gap in factors of production can be filled by appropriate financial and banking policies to increase access to finance and boost physical capital accumulation, a sound business environment to attract investors and boost long-term productivity, and a reduction in macroeconomic risks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet